Експериментальний стенд для дослідження теплоелектрогенеруючих агрегатів на базі рідинно-парових струминних апаратів - Шарапов, Сергій Олегович; Вербицький, Антон Романович; Євтушенко, Святослав Олександрович; Хованський, Сергій Олександрович; Ковязін, Олексій Сергійович; Sharapov, Serhii; Verbytskiy, Anton; Yevtushenko, Sviatoslav; Khovanskyi, Serhii; Koviazin, Oleksii (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті описано мету та завдання експериментальних досліджень теплоелектрогенеруючих агрегатів на базі рідинно-парових струминних апаратів. Для визначення завдань експериментальних досліджень було проведено критичний аналіз сучасного стану досліджень схемних рішень когенераційних систем для генерації теплової та електричної енергії, серед яких установки на базі міні-ТЕЦ та на базі теплових насосів. Отже, необхідно провести експериментальні дослідження пропонованого авторами теплоелектрогенеруючого агрегату на базі рідинно-парового струминного апарату, які б підтвердили проведені числові розрахунки та визначили режимні параметри, за яких його ефективність буде максимальною. У статті наведено схему та опис експериментальної установки для досліджень теплоелектрогенеруючих агрегатів на базі рідинно-парових струминних апаратів. Програма та методика містять діапазон зміни режимних та геометричних параметрів при проведенні експериментальних досліджень. Запропоновано схему підключення блоку конденсаторів до електрогенератора та наведено опис пропонованих контрольно-вимірювальних приладів в характерних точках циклах. /// EN: This article describes the objectives and tasks of experimental studies of combined heat and power generation units based on liquid-vapor jet devices. To define the objectives of the experimental studies, a critical analysis was conducted of the current state of research on design solutions for cogeneration systems for the generation of thermal and electrical energy, including installations based on mini-CHP plants and heat pumps. Based on a review of the literature, it can be concluded that the modern energy sector has not developed highly efficient thermal and electrical power generation units with a capacity of up to 0.5 MW that could meet the needs of individual consumers. The literature review also revealed that there is currently no design solution capable of meeting the thermal and electrical energy needs of individual consumers. The authors propose a design solution for a combined heat and power unit based on a liquid-vapor jet device, which combines all the advantages of a mini-CHP plant and a heat pump system. The theoretical studies conducted by the authors allow us to conclude that the use of such units in distributed generation systems is feasible. Therefore, it is necessary to conduct experimental studies of the heat and power generation unit proposed by the authors, based on a liquid-vapor jet device, which would confirm the numerical calculations and determine the operating parameters under which its efficiency will be maximized. The article presents a diagram and description of an experimental setup for studying thermoelectric power generation units based on liquid-vapor jet devices. The program and methodology include a range of operating and geometric parameters for conducting experimental research. A connection diagram for the capacitor bank to the electric generator is proposed, and a description of the proposed control and measuring instruments at characteristic points in the cycles is provided. The methodology for processing the results of experimental studies of a heat and power generation unit based on a liquid-vapor jet device is also described, including the determination of the main errors in direct and indirect measurements.
Experimental stand for researching heat-&-electricity generating aggregates based on liquid-vapor jet devices
Keywords: рідинно-паровий струминний апарат; виробництво тепла та електроенергії; експериментальні дослідження; геометричні параметри; ефективність; доступна та чиста енергія; сталий розвиток міст та громад; liquid-vapor jet device; heat-&-electricity generating; experimental research; geometric parameters; efficiency; affordable and clean energy; sustainable cities and communities